The Birth and Adaptation of Evaluation Theories - Marvin C. Alkin; Michael Q. Patton (Journal of MultiDisciplinary Evaluation)
Background: Evaluation theories as we know them are prescriptions by prominent evaluators about what they believe to be an appropriate way to conduct  evaluations. How do these prescriptions come about? In this paper we examine the various influences on the creation and subsequent modification of these prescribed evaluation theories. Inquiry into evaluation theories has a long history. What is new is inquiry into the evolution of theories.This makes theory formulation dynamic rather than static. Influences identified by Alkin in a National Society for the Study of Education yearbook (1989) serve as an initial guide to this inquiry. An examination of Michael Q. Patton's writings and shaping experiences provides further case study insights about the evolution of his utilization-focused evaluation theory and its offshoots.